2017
DOI: 10.1007/s12671-017-0767-1
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness, Acceptance and Defusion Strategies in Smokers: a Systematic Review of Laboratory Studies

Abstract: The psychological flexibility model (PFM) provides a framework for understanding and treating behavioural dysregulation in addictions. Rather than modulating the intensity of subjective experience, interventions based on, or consistent with, the PFM (PFM interventions) seek to alter the individual’s relationship to internal states, such as craving, negative affect and drug-related thoughts, using mindfulness, acceptance and related strategies. Experimental (non-clinical) studies in smokers have examined the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Various comparisons of ACT components and EA procedures in the management of smoking behaviour can now be found in the literature [see Serfaty, Gale, Beadman, Froeliger and Kamboj (2017) for a recent systematic review of mindfulness, acceptance and defusion laboratory-based smoking studies]. However, one investigation in particular, in combination with the aforementioned Erskine et al…”
mentioning
confidence: 99%
“…Various comparisons of ACT components and EA procedures in the management of smoking behaviour can now be found in the literature [see Serfaty, Gale, Beadman, Froeliger and Kamboj (2017) for a recent systematic review of mindfulness, acceptance and defusion laboratory-based smoking studies]. However, one investigation in particular, in combination with the aforementioned Erskine et al…”
mentioning
confidence: 99%
“…In contrast, other lab-based mindfulness studies (particularly in smokers) have demonstrated a larger downregulation of craving following brief mindfulness instructions. However, these effects have generally been observed when mindfulness was compared with an inactive control condition (see review by Serfaty et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other clinical trials suggest that, despite not directly aiming to reduce craving, reductions in craving are nonetheless observed following mindfulness-based treatments (e.g., Bowen et al, 2009 ; Davis et al, 2014 ; Garland et al, 2016 ; see Li et al, 2017 for other examples). Laboratory experiments have also shown acute reductions in craving following mindfulness in smokers, although this effect is most robust when mindfulness strategies are compared with inactive control strategies (see Serfaty et al, 2017 ). Alternatively, some laboratory studies have shown that, relative to active control strategies (e.g., distraction or reappraisal), brief mindfulness-like strategies result in increased ( Szasz et al, 2012 ), or limited reductions in, cue-induced craving ( Murphy and McKillop, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The psychopathology model of acceptance and commitment-based interventions emphasizes the need to reduce the preponderance of the conceptual past and future, dysfunctional behaviors, attachment to the theoretical self, cognitive fusion and experiential avoidance and increase the bond with values 13 . Although in the literature many studies have been conducted on smoking cessation with acceptance and commitment-based approaches 15,16 , there is no study on this issue in Turkey. In this respect, its application to different cultures is believed to provide evidence for the field.…”
Section: Introductionmentioning
confidence: 99%